Premium Scarves Enterprise / Ummi Ilham Sabri... [et al.] - Sabri, Ummi Ilham; Mohd Norman, Norlyana Izati; Khairudin, Khairunnisa; Hasbullah, Hasliza; Shafie, Nur Farisha Balqis (2021)
Our company Our company is a manufacturing company that manufactures and sells various types of high-quality scarves such as Premium Pleats Shawl, Premium Cloud Cotton Shawl and Premium Print. The company has now registered with SSM and has sold the hijab to the market widely. Management We have five key people who will run the business and include two employees. All important people including have positions such as General Manager, Administrative Executive, Marketing Executive, Operations Executive, Finance Manager and two Operations Staff. Our product Premium Pleats Shawl Premium Cloud Cotton Shawl Premium Print The market According to Women’s Magazine in 2016, the expansion of accessories such as headscarves or shawls is currently very rapid as accessories are so capable of attracting women in terms of the accessories used to beautify their appearance and cover the genitals. Women's accessories are not only in terms of jewellery, scarves, or shawls but bags, shoes, wallets and so on. However, scarves have attracted more attention than other types of accessories. Therefore, this study is more focused on scarves. These statistics clearly show that scarves are more popular in the society nowadays with fashions following the current trends.